Natural variation in teosinte at the domestication locus teosinte branched1 (tb1) - Vann, Laura; Kono, Thomas; Pyhäjärvi, Tanja; Hufford, Matthew B.; Ross-Ibarra, Jeffrey (PeerJ, 2015)
The teosinte branched1(tb1) gene is a major QTL controlling branching differences between maize and its wild progenitor, teosinte. The insertion of a transposable element (Hopscotch) upstream of tb1 is known to enhance the gene’s expression, causing reduced tillering in maize. Observations of the maize tb1 allele in teosinte and estimates of an insertion age of the Hopscotch that predates domestication led us to investigate its prevalence and potential role in teosinte. We assessed the prevalence of the Hopscotch element across an Americas-wide sample of 837 maize and teosinte individuals using a co-dominant PCR assay. Additionally, we calculated population genetic summaries using sequence data from a subset of individuals from four teosinte populations and collected phenotypic data using seed from a single teosinte population where Hopscotch was found segregating at high frequency. Genotyping results indicate the Hopscotch element is found in a number of teosinte populations and linkage disequilibrium near tb1 does not support recent introgression from maize. Population genetic signatures are consistent with selection on the tb1 locus, revealing a potential ecological role, but a greenhouse experiment does not detect a strong association between the Hopscotch and tillering in teosinte. Our findings suggest the role of Hopscotch differs between maize and teosinte. Future work should assess tb1 expression levels in teosinte with and without the Hopscotch and more comprehensively phenotype teosinte to assess the ecological significance of the Hopscotch insertion and, more broadly, the tb1 locus in teosinte.
Keywords: Transposable element; Domestication; Teosinte; Teosinte branched1; Maize